[PP.12.08] EFFECTS OF MELATONIN ON THE PRODUCTION OF ADIPONECTIN AND THE EXPRESSION OF ADIPONECTIN RECEPTOR IN THE VISCERAL ADIPOSE TISSUE OF AGING MICE. (September 2016) - Rosei, C. Agabiti; Favero, G.; Rezzani, R.; De Ciuceis, C.; Rodella, L.F.; Porteri, E.; Rosei, E. Agabiti; Rizzoni, D.
Abstract : Objective: It has been previously demonstrated that inflammation in adipose tissue may be implicated in vascular dysfunction (Circulation 2009; 119(12):1661–1670). A senescence-accelerated prone mouse (SAMP8) is a model of age-related cognitive decline and vascular dysfunction. Several studies demonstrated that SAMP8 suffers from increased oxidative stress and that accelerated senescence was associated with increased oxygen radicals synthesis. We have also recently demostrated that the anticontractile effect of perivascular fat is impaired in a senescence-accelerated prone mouse, compared with control senescence-resistant mice (SAMR1). A long-term treatment with melatonin seems to decrease contractile responses to norepinephrine in mesenteric small arteries of SAMP8, thus restoring an anticontractile effect, probably through antioxidant mechanisms. However, it is not know whether melatonin is able to modulate the production of adiponectin and/or the expression of adiponectin receptors. Therefore, the aim of the study was to investigate the production of adiponectin and/or the expression of adiponectin receptors in the visceral adipose tissue of SAMP8 before and after chronic treatment with melatonin. Design and method: We investigated 7 SAMP8 and 7 SAMR1 treated for 10 months with melatonin (MEL, 10 mg/kg/day), an endogenous indoleamine with antioxidant and vasculoprotective properties, as well as 7 SAMP8 and 7 SAMR1 untreated controls (CTR) kept untreated for 10 months. Visceral fat (perirenal fat) was obtained by dissection, and the adiponectin content, as well as the expression of adiponectin receptor were evaluated by immunohistochemistry. Results: Results are shown in the figure (* p < 0.05 vs SAMR1 CTR; # p < 0.05 vs SAMR1 + MEL; + p < 0.05 vs SAMP8 + MEL). The adiponectin content, as well as the expression of adiponectin receptor were reduced in untreated SAMP8 compared with untreated SAMR1. Treament with MEL was able to increase the production of both proteins in SAMP8. Figure. No caption available. Conclusions: Melatonin treatment is able to increase the production of adiponectin and the expression of adiponectin receptor in the visceral fat of aging mice. This observation might contribute to explain the improvement of the anticontractile action of perivascular fat observed in the mesenteric small resistance arteries of SAMP8 mice after chronic treatment with MEL.